The Right of the Child to a Clean Environment - Fijalkowski, Agata (Taylor and Francis, 2017)
"This title was first published in 2000: A discussion on the right of a child to a clean environment. It links two important contemporary issues: human rights and the environment. The volume consists of the extended versions of some of the papers which were presented at a workshop on "The Right of a Child to a Clean Environment", held at Queen Mary and Westfield College, University of London, in 1997, and there are also some additional contributions. The workshop participants included Michael Anderson and Sylvia Bluck, Harry Post, Holly Cullen and Olufemi Elias. The additional contributors include Veronic Wright, Maria G. Doglioli and Soledad Aguilar. There are essays on general issues, selected case studies and annexes."--Provided by publisher